COGNITIVE BEHAVIOR THERAPY UNTUK MENURUNKAN PERILAKU OBSESIF KOMPULSIF PADA REMAJA - Risna Amalia (Prosiding Seminar Nasional Multidisiplin, 2019)
This study aims to intervene in one of the students who is in Al-Azhar Gresik High School. The subject has obsessive compulsive behavior in the form of using a handbody on the sole of the foot repeatedly. Researchers provide interventions in the form of cognitive behavior therapy as interventions to reduce obsessive compulsive behavior, and to improve mental health in schools. This therapy aims to oppose wrong thoughts and emotions by presenting evidence that contradicts beliefs about the problem at hand. The method used in this research is qualitative with a case study approach. Subjects were female who were 16 years old and had obsessive compulsive behavior for 14 months. The cognitive behavior therapy procedure is first, the subject is asked for relaxation in the form of progressivrizkie muscle relaxation to learn to stretch and relax various muscle groups and learn to notice the difference between tension and relax. Second, cognitive restructuring, reducing the anxiety level of the subject caused by negative thoughts and replacing them with more positive thoughts, and. Third, exposure with response prevention, to overcome obsessive compulsive behavior. Where the subject is faced with a situation of having the belief that must perform the usual ritual behavior but the subject is prevented from doing the ritual. If the subject can prevent not doing the ritual and it turns out that something terrible did not happen, this can help in changing the subject's belief in compulsive behavior. The intervention consisted of eight sessions with two sessions a week and 60 minutes each for each session. The results of this study indicate that cognitive behavior therapy is effectively used to reduce the subject's obsessive compulsive behavior, which is shown by decreasing levels of anxiety, negative thinking and compulsive behavior. Keywords: Cognitive behavior therapy, obsessive compulsive behavior, adolescents